The impacts of mid‐treatment CBCT‐guided patient repositioning on target coverage during lung VMAT. Issue 4 (7th February 2017) - Mathieu, Dominique; Campeau, Marie‐Pierre; Bedwani, Stéphane; Roberge, David; Doucet, Robert; Zerouali, Karim; Bahig, Houda; Vu, Toni; Lambert, Louise; Masucci, Laura; Filion, Edith
Abstract: Introduction: The purpose of this study is quantify intrafraction motion (IFM) during lung volumetric‐modulated arc therapy (VMAT) and evaluate the impact of mid‐treatment cone beam computed tomography (CBCT)‐guided patient repositioning on target coverage. Method: This analysis included lung tumours treated with VMAT to 50–60 Gy in 3–5 fractions. Treatment planning was based on four‐dimensional CT scans from which internal tumour volumes (ITV) were derived. An isotropic 5 mm margin was added to obtain the final planning target volume (PTV). Patients were treated supine with a customized dual vacuum immobilization device (BodyFIX, Elekta, Sweden). All patients underwent pre and mid‐treatment CBCTs. Following each CBCT, a rigid registration was performed by a radiation oncologist. IFM was defined as the target displacement from pre to mid‐treatment CBCT. For patients with an IFM vector ≥5 mm, a post hoc dose calculation analysis was performed to assess the dosimetric impact of CBCT‐guided repositioning. Results: Ninety–seven patients (367 fractions) were included. Mean (±SD) overall treatment time was 53:02 ± 13:08 min. Mean time for mid‐treatment CBCT scan acquisition and patient repositioning was 15:49 ± 4:14 min. Mean IFM vector was 1.5 ± 1.4 mm (max = 8.1 mm) and was <5 mm in 354/367 (96%) of fractions. For all 13 fractions with an IFM vector ≥5 mm, dose calculation analysis of worst‐case scenario indicates that ITV coverage would have remained ≥95% without mid‐treatment repositioning. Conclusion: For 96% of fractions, the IFM vector was within the 5 mm PTV margin. Mid‐treatment CBCT‐guided couch repositioning did not significantly impact ITV coverage and prolonged treatment duration.